Can digital value chain tracing drive the sustainability transition? A closer look at Peruvian cocoa - Steinke, Jonathan; Ivanova, Yovita; Jones, Sarah; Minh, Thai Thi; Sanchez Bogado, Andrea Cecilia; Sánchez Choy, José G.; Mockshell, Jonathan; Min (2023)
Key messages: - Growing consumer demand for agri-food commodities grown under responsible social and environmental conditions creates financial incentives for the private sector transition towards sustainable sourcing. - Verifying farming sustainability is challenging in smallholder context due to complex supply chains. But novel digital technologies allow tracing commodities back to farms of origin, enabling increased transparency on farm-level practices. - Implementing digital traceability systems requires commitments by various value chain players, so financial gains from higher market demand must be shared equitably. - Given limited external supervision, careful choice of sustainability metrics is important to ensure data accuracy and to limit opportunities for fraud. - Setting up tracing systems may require investments in farmers’ digital capacity and co-design of user-friendly interfaces. Where increased consumer demand does not cover costs, public payments for ecosystem services can uphold incentives for farmers’ sustainability transition.